Mengungkap Pesan Ekologis dalam Novel Negeri Lintasan Petir Karya Gerson Poyk: Studi Ekokritik - Juanda, Juanda; Afandi, Iswan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sriwijaya, 2024)
The connection between literature and nature is vital, considering the richness of nature and the diversity of ecosystems that exist. Authors convey many ecological messages through literary works such as novels. This study examines the representation of nature in the novel Negeri Lintasan Petir by Gerson Poyk using Greg Garrard's ecocritical theoretical framework. The data source is the text in the novel Negeri Lintasan Petir in words, phrases, clauses, or sentences. Data analysis was done using an interactive analysis model technique assisted by Nvivo R1 software. The results showed that the author, Gerson Poyk, narrates pollution, wilderness, disasters, settlements, animals, and the earth. Based on the data, the author more dominantly narrates the relationship between humans and nature related to the phenomenon of settlements, namely the character Indra, who criticizes development in Jakarta because of government policies towards development that are not ecological, KKN culture and an uneven education system, especially transmigration areas. In contrast, the least narrated is the phenomenon of the earth. This research contributes to the government's making laws on environmental conservation, and this novel can be used as teaching material for teachers and lecturers so that students are environmentally aware. Future research can be done by analyzing the reception of students and college students towards the novel Negeri Lintasa Peti by Gerson Poyk.